Application of Sport Science on Development of Exercise Model Strokes Badminton Based on Footwork - Firmansyah Dlis; Aridhotul Haqiyah; Nurul Hidayah; Dani Nur Riyadi (STKIP Singkawang, 2019)
The purpose this study will be useful for developing and implementing a training model design strokes-based footwork. This product was expected to be an alternative model of exercise strokes-based badminton footwork for middle school students aged 12-15. The method used in this study is research and development of ADDIE. This research was conducted at SMP 74 Jakarta within 4 months in May - September 2018 with research steps: (1) Needs Analysis, (2) Model Development Planning, (3) Development of Exercise Model Design, (4) Expert Validation and Model Revision, (5) Evaluation and Revision Test. Based on the data obtained from the results of the study consisting of expert validation, group trials and effectiveness tests, and discussion of the results of the study, it can be concluded as follows: (1) The model of training footwork for beginner's that the researchers have developed obtained 35 items that are worth using, (2) Based on the results of the footwork badminton test, t = 3,920, db = 58 and sig. (2-tailed) or p-value = 0,000 <0.05. This means that the training model footwork badminton for beginners is more effective in improving the basic technical skills of badminton footwork.